1967
DOI: 10.1111/j.1748-1716.1967.tb03719.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Glycogen during Prolonged Severe Exercise

Abstract: HERMANSEN, I-., E. HULTMAN and B. SALTIN. Muscle glycogen during prolonged severe exercise. Acta physiol. scand. 1967. 71. 129-139. 10 well trained and 10 untrained subjects worked to complete exhaustion on a bicycle ergometer with work loads averaging 77 (76-87) per cent of their individual maximal aerobic power. Determinations of glycogen used by working muscles (biopsy of lateral portion of the quadriceps femoris muscles) and of combusted carbohydrate (Vos and R Q ) were performed at certain intervals fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
300
1
10

Year Published

1971
1971
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 657 publications
(324 citation statements)
references
References 17 publications
13
300
1
10
Order By: Relevance
“…Under these conditions, the rate of muscle glycogen utilization is high, although a certain amount still remains in muscle after exhaustion (14). However, in exercise performed below AT there is no lactate accumulation and exercise duration can be limited by glycogen depletion, which limits energy production, since carbohydrates are essential to Krebs cycle function (15). Since many studies (5,16), but not all of them (9), have demonstrated that caffeine can increase intramuscular triacylglycerol and/or extramuscular FFA, there may be a glycogen economy (Randle effect) retarding the beginning of exhaustion only during exercise performed below AT.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Under these conditions, the rate of muscle glycogen utilization is high, although a certain amount still remains in muscle after exhaustion (14). However, in exercise performed below AT there is no lactate accumulation and exercise duration can be limited by glycogen depletion, which limits energy production, since carbohydrates are essential to Krebs cycle function (15). Since many studies (5,16), but not all of them (9), have demonstrated that caffeine can increase intramuscular triacylglycerol and/or extramuscular FFA, there may be a glycogen economy (Randle effect) retarding the beginning of exhaustion only during exercise performed below AT.…”
mentioning
confidence: 99%
“…Moreover, exhaustion does not seem to occur due to the depletion of glycogen sources. Some studies have found muscular glycogen economy during endurance exercise after caffeine ingestion (15,18).…”
mentioning
confidence: 99%
“…In humans, muscle glycogen stores represent an essential energy source during submaximal exercise, and depletion of muscle glycogen stores promotes muscle fatigue (15)(16)(17)(18). Due to the close homology between the liver and skeletal muscle glycogen phosphorylase isoenzymes, the available GPi do not demonstrate tissue specificity (1,3,19) and thus may impair glycogen mobilization in skeletal muscle.…”
mentioning
confidence: 99%
“…Glycogen deposits are important for maintaining physical performance during endurance exercises (25)(26)(27)(28)(29). We previously reported that young (12-wk-old) mice fed a sea snake lipid diet had significantly higher levels of muscle glycogen as well as plasma glucose levels than animals fed a lard diet following a 5 min swimming exercise; and so the improved swimming endurance is likely intimately related with the glycogen and plasma glucose metabolism as energies for swimming exercise in young mice (10).…”
Section: Discussionmentioning
confidence: 99%